Variable Incremental Controller of Permanent-Magnet Synchronous Motor for Voltage-Based Flux-Weakening Control - Hyunjae Lee; Gunbok Lee; Gildong Kim; Jingeun Shon (Energies, 2022)
This study presents a variable incremental controller for flux-weakening control in the high-speed operation area of a permanent-magnetic synchronous motor (PMSM). In general, voltage-based flux-weakening control utilizes a reference voltage and a PI controller to generate a flux component current. In this paper, the voltage-based flux-weakening control is performed using the variable incremental controller instead of the PI controller. The variable incremental controller can control the flux component current using only the maximum speed and maximum current of the motor. A method for properly setting an appropriate variable incremental controller using acceleration is additionally presented. A variable incremental controller is applied and, accordingly, the overshoot of the motor speed can be reduced and the speed error of the motor can be minimized by reducing the difference between the actual motor and targeted accelerations. This method can simplify the design of a controller that utilizes flux-weakening control and can be applied to railroad cars whose acceleration does not alter frequently to increase the effect of motor control.